Math Makes Sense : A Constructivist Approach to the Teaching and Learning of Mathematics - Quintero, Ana Helvia and Rosario, Hector (Singapore : World Scientific Pub. Co., 2016)
"The methods for teaching mathematics usually follow the structure of mathematics. The problem with this is that the structure of mathematics took centuries of elaboration to develop and is not the same as how one originally experiences mathematics. Based on research of how mathematics is actually learned, this book presents an innovative approach for teaching mathematics that will engage pupils and can have lifelong benefits for how they take on board more advanced mathematical topics. Math Makes Sense! makes use of the realistic mathematics education (RME) philosophy, which bridges the gap between informal mathematics learning (such as in day-to-day life) and more formal teaching in school. Many real-life situations as examples for learning are included, as well as different mathematical and logic puzzles that will stimulate learning and foster understanding. The ideas presented are not confined to one national curriculum and so can be helpful worldwide to teachers/ instructors (both in practice and those still in training), private tutors, homeschooling parents, and educational researchers."--Provided by publisher.
Fostering the learning of mathematics -- Construction of concepts and mathematical interpretations -- Numbering -- Addition and subtraction -- Multiplication and division -- Fractions, decimals, and percentages -- Measurement -- Exploring space -- Probability and statistics -- Patterns, relations, and functions -- The joy of puzzles -- Technology : a tool for analysis and interpretation -- Assessment -- Concluding remarks.
Title from PDF file title page (viewed March 23, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Mathematics -- Study and teaching; Electronic books